Hydrodynamics of the atomic force microscope - Clarke, Richard John (2005)
With a proven ability to uncover fundamental biological processes, the atomic force microscope (AFM) represents one of the most valuable and versatile tools available to the biophysical sciences. We study the unsteady small-scale flows generated within the AFM by its sensing probe (a long thin cantilever), which have received relatively little attention to date, yet which are increasingly relevant in an age of microdevices.